Radioactivity levels in some wild edible mushroom species in Turkey - Turhan, Şeref; Köse, Abdullah; Varınlıoğlu, Ahmet (Isotopes in Environmental and Health Studies & Taylor & Francis, 2007)
Eleven different wild-growing edible mushroom species collected from various regions of Turkey were analysed for their content of 137Cs, 40K, 226Ra and 232Th using a high-resolution gamma-ray spectrometry. Specific activities of 226Ra and 232Th were generally below detection limits. The specific activities of 137Cs and 40K ranged from 2.4 ± 0.3 to 109.0 ± 7.3 Bq kg−1 with a mean of 28.4 ± 27.2 Bq kg−1 (dry matter) and 715.5 ± 50.1 to 1779.0 ± 163.7 Bq kg−1 with a mean of 1150.8 ± 315.2 Bq kg−1 (dry matter), respectively. The mean annual effective dose of 137Cs and 40K through mushrooms were estimated to be (7.0 ± 6.0) × 10−3 μSv and 0.13 ± 0.03μSv, respectively. The overall intake of 137Cs is quite low and no significant contamination was found in collected mushroom species. The highest contents of 137Cs and 40K among the analysed mushrooms were in Morchella esculenta and Stropharia coronilla, respectively
Keywords: Cesium-137; Effective dose; Gamma ray; Mushrooms; Potassium-40; Radium-226; Specific radioactivity; Thorium-232